(3GdebGeI GdfNdjI hTQMgGs - (3Ydj Hf YHO Gddg Hf eMeO Hf eMeO GdLPGej GdeGdbj GdfHGgj, GHf GdMSf,J (B792 (3g` s
(3ChdgG (B:s
(3bdJ CNGWH ef CLQi ef GdSQGJ PcQ GdYQGb Chd GdTQM(B: (3CeG HYO MeO Gddg GdYdi GdYXje aEf cfJ bO CedjJ s
(3BNQgG (B:s
(3jYJeO ef jba YdjgG ef GdBf Edi jhe GdeYGO hGdQMeGJ hGdHQcGJ JeJ GdebGeI hjJdhgG GdTQM BNQ GdTQM(B: (3hjG ef CeQg EPG CQGO TjFkG jbhd dg cf ajchf GdfUGFM s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3JJab ai Chd GdebGeI hBNQgG hcPdc ai Chd GdTQM hBNQg HGNJdGa ai HYV GdCdaGXs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B306s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B99 s
Keywords: (3GdCOHs